Construction of Auditor Profession Ethics in The Era of Digital Disruption: a Phenomenological Study of Public Accounting Firm in Surabaya - Nur Islamiati Sulaiman; Sri Trisnaningsih; Hero Priono (PT. Maju Malaqbi Makkarana, 2026)
This study aims to explore auditors' experiences in digital auditing practices, the meaning of professional ethics, and ethical dilemmas in the context of digital disruption using a phenomenological approach. The study was conducted at a Public Accounting Firm (KAP) in Surabaya, with auditors who had experience in technology-based audits as informants. Data were collected through in-depth interviews, observation, and documentation, then analyzed using a phenomenological approach supported by NVivo software. The results show that digital auditing practices are still dominated by the use of simple technologies such as Microsoft Excel for data processing, analysis, and audit documentation. Although technology increases efficiency, auditors still do not fully rely on the system and still use professional judgment to maintain the reliability of audit results. Professional ethics is understood as a primary foundation that remains valid, but is reinterpreted in the digital context, particularly related to efficiency pressures and technological risks. Ethical dilemmas arise due to time constraints, incomplete data, and client demands, so auditors tend to prioritize the sufficiency of evidence and prudence in decision-making. Overall, this study concludes that digital disruption does not change the fundamental values ​​of auditors' professional ethics, but rather reconstructs their meaning through work experiences and professional interactions.